Serum Uric Acid Levels Predict Mortality Risk in Male Amyotrophic Lateral Sclerosis Patients - Xu, Liu-Qing; Hu, Wei; Guo, Qi-Fu; Xu, Guo-Rong; Wang, Ning; Zhang, Qi-Jie (Frontiers in Neurology, 2021)
Objective: To explore the associations between serum uric acid levels with survival in male and female ALS patients. Methods: A longitudinal cohort study was carried out including 313 sporadic and 16 familial ALS patients with repeated serum uric acid measurements. Multivariate Cox regression models were used to evaluate the survival-related factors. Results: There were 207 male and 122 female, and the mean age of onset was 55.7±11.2 years old. The male patients had significantly higher baseline uric acid levels than that in female patients (342.4 ± 91.4μmol/L vs. 279.3 ± 71.4μmol/L; p<0.0001). The uric acid levels were inversely associated with the decline rate of ALSFRS-R per month (ΔALSFRS-R). After multivariate Cox regression analysis, a survival advantage was found in male, but not female, with higher serum uric acid levels. In males, a shorter diagnostic delay (≤10 m), lower BMI at baseline (≤18.70 kg/m2), faster disease progression (ΔALSFRS-R >0.63), and lower baseline uric acid levels (≤ 292μmol/L, HR: 1.936; 95%CI: 1.334-2.810) were associated with a shorter survival. During follow-up, the serum uric acid levels were not significantly altered over time. Conclusion: There is an inverse correlation between baseline serum uric acid levels and risk of death, prominently in male ALS patients.